Genetic and epigenetic changes during the invasion of a cosmopolitan species (Phragmites australis). Issue 13 (11th June 2018) - Liu, Lele; Pei, Cuiping; Liu, Shuna; Guo, Xiao; Du, Ning; Guo, Weihua
Abstract: While many introduced invasive species can increase genetic diversity through multiple introductions and/or hybridization to colonize successfully in new environments, others with low genetic diversity have to persist by alternative mechanisms such as epigenetic variation. Given that Phragmites australis is a cosmopolitan reed growing in a wide range of habitats and its invasion history, especially in North America, has been relatively well studied, it provides an ideal system for studying the role and relationship of genetic and epigenetic variation in biological invasions. We used amplified fragment length polymorphism (AFLP) and methylation‐sensitive (MS) AFLP methods to evaluate genetic and epigenetic diversity and structure in groups of the common reed across its range in the world. Evidence from analysis of molecular variance (AMOVA) based on AFLP and MS‐AFLP data supported the previous conclusion that the invasive introduced populations of P. australis in North America were from European and Mediterranean regions. In the Gulf Coast region, the introduced group harbored a high level of genetic variation relative to originating group from its native location, and it showed epigenetic diversity equal to that of the native group, if not higher, while the introduced group held lower genetic diversity than the native. In the Great Lakes region, the native group displayed very low genetic and epigenetic variation, and the introduced one showed slightly lower genetic and epigenetic diversity than the original one. Unexpectedly, AMOVA and principal component analysis did not demonstrate any epigenetic convergence between native and introduced groups before genetic convergence. Our results suggested that intertwined changes in genetic and epigenetic variation were involved in the invasion success in North America. Although our study did not provide strong evidence proving the importance of epigenetic variation prior to genetic, it implied the similar role of stable epigenetic diversity to genetic diversity in the adaptation of P. australis to local environment. Abstract : We first compared patterns of genetic and epigenetic variation in Phragmites australis grew in a common garden collected around the globe using amplified fragment length polymorphism and methylation‐sensitive amplification polymorphism methods. We collected samples from native and introduced groups in North America and the possible original groups for the introduced groups, so we were able to detect the direction and the magnitude of genetic and epigenetic changes during the invasion of P. australis . Our results suggested that intertwined changes in genetic and epigenetic variation were involved in the invasion success in the North America.